Effect of Cooking Methods on Nutritional Quality of Sea Lettuce (Ulva lactuca) Flakes - Ardiba R. Sefrienda; Jasmadi Jasmadi; Hilda Novianty; Indyaswan T. Suryaningtyas; Rachma Wikandari (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Proximate of Ulva lactuca after cooking treatments were analyzed. The cooking treatments carried out in this study were roasted and boiled-roasted Protein quality such as in-vitro digestibility, protein solubility, and amino acids composition of Ulva lactuca after cooking treatments were analyzed The result showed that boiled-roasted samples had the highest protein content, amino acid score and essential acid index, and predicted-protein efficiency ratio   Abstract Plant-based protein has been increasingly demanded as a sustainable protein source. Sea lettuce (Ulva lactuca) is one of the potential sources as plant protein due to its high protein content. During processing, the sea lettuce is exposed to heat which might affect its nutrition, particularly the protein quality. This study aimed to evaluate two different cooking processes on the nutritional quality of the sea lettuce based on the proximate and protein quality analyses. The samples were raw, roasted, and boiled-roasted sea lettuce. All treatment using temperature 100°C. The protein quality was assessed by in-vitro protein digestibility, solubility, and amino acid profiles. The result showed that boiling treatment followed by roasting treatment had significantly higher protein content, amino acid score and essential amino acid index, and predicted-protein efficiency ratio compared with the value of roasting treatment only. It resulted in protein content of 18.87% (dry basis), amino acid score of 37.96%, essential amino acid index of 79.41% and predicted-protein efficiency ratio of 2.58. Therefore, boiling followed with roasting process is recommended to maintain the nutrition quality of sea lettuce.